Social Awareness & Technology Development of Hybrid Marketing Models With Reference to Amazon & E-bay - Kumar Sharma, Dr. Veeresh (JOURNAL OF BUSINESS MANAGEMENT & QUALITY ASSURANCE, 2022)
The study deals with marketing models of Amazon & E-bay, the most famous international companies who deal in marketing their products and services via internet. The purpose of study was to identify the impact of use of technology in hybrid marketing models of Amazon and E-bay and demonstrate such impact on the sales expenditure and sales revenue has been taken. The study reveals that there is perfect Correlation between sales revenue and sales expenditure of Amazon & E-bay which indicates that as the sales revenue increases the sales expenditure may also increase at the same rate .The study also spotlighted the various channels through which the marketing is carried out via internet .It also describes the strategic reasons, pull & push factors for utilization of technology which makes a simple marketing model as a hybrid model of marketing. However, in today’s digital age there is no survival for MNC’s without entering in digital world because these are the practices which enhance the company’s sales, expansions plans, meet with consumer requirements, helps to cope up with rivals, meet with consumer requirements. Above all it provides an easy reach to consumer and leaded by consumer satisfaction. So there is still a need to invest in development & usage of technology in marketing models owing to development of communication network are still on growth stage especially a developing countries like India. Key Words:Social, Awareness, Hybrid, Marketing, Amazon